Effect of age, electrode array, and time on cochlear implant impedances. (1st November 2020) - Velandia, Sandra; Martinez, Diane; Goncalves, Stefania; Pena, Stefanie; Bas, Esperanza; Ein, Liliana; Prentiss, Sandra; Telischi, Fred; Angeli, Simon; Dinh, Christine T.
Abstract : Objectives: To determine the impact of age, electrode array, and time on impedance patterns in cochlear implant (CI) patients. Methods: A retrospective case review was performed on 98 patients implanted with the CI24RE perimodiolar (PM) and CI422 lateral wall (LW) arrays between 2010 and 2014 to assess impedances at the 1 week and 3–6 month visit after initial stimulation (IS). Results: With respect to age, impedances were higher in young patients compared to older patients in the middle and apical turns. With time, there were significant reductions in impedances across most electrodes. Electrode array type also had a significant impact on impedance measurements with PM and LW arrays having higher impedances in the basal turn and apical turns, respectively. Furthermore, PM arrays demonstrated significantly lower impedances in the middle and apical turn with time, when compared to LW arrays. Conclusions: Age, electrode array, and time can independently affect CI impedances. Moreover, we show that PM arrays may be advantageous to LW arrays, due to demonstrated lower impedances in the middle and apical turns long term. Understanding the impact of impedance on speech discrimination and determining the intracochlear processes that contribute to differences in impedance are future research directions.